Seguimiento farmacoterapéutico en pacientes con hipertensión arterial no controlada y dislipidemia atendidos en un Hospital de Iquitos, año 2023 - Tello Gómez, Katherine Hann (2024)
Uncontrolled arterial hypertension and dyslipidemia are pathologies with a high risk of cardiovascular morbidity and mortality. The specific objectives were to identify the demographic characteristics, measure the efficacy of pharmacotherapeutic follow-up using the Morisky Green test in patients with uncontrolled hypertension and dyslipidemia, attended in the office of the Home Care Program -PADOMI of Hospital III- Iquitos, EsSalud 2023; quantitative study type, analytical, prospective, quasi-experimental design; the population was 69 patients with arterial hypertension and 41 patients with dyslipidemia; the methodology used was pharmacotherapeutic follow-up to determine drug-related problems - DRPs, Morisky-Green test, for adherence to treatment; the results obtained in both pathologies were more frequent in the female sex, ages between 27 to 59 years; the DRPs were: 70.8% DRP4 and 52.8% DRP5, therapeutic adherence with 66.7% in patients with uncontrolled arterial hypertension and 77.8% in patient with dyslipidemia. We conclude that pharmacotherapeutic follow-up contributes to improving adherence to drug treatment in patients with uncontrolled hypertension and dyslipidemia, improving the health of patients with both pathologies.